Postbiotic Potential of Lactic Acid Bacteria Strains in Functional Minimally Processed Oranges - Paola Foti; Flora Valeria Romeo; Gloria Sciuto; Maria Concetta Strano; Maria Allegra; Nunziatina Russo; Cinzia Caggia (Applied Sciences)
The global market for fresh, ready-to-eat products has grown rapidly, leading to some microbiological safety concerns. Lactic acid bacteria (LAB), along with their metabolites, represent a green alternative to chemical preservatives. For this purpose, the cell-free supernatant of LAB strains previously isolated from fruits and their potential antibacterial effects against pathogens commonly found in minimally processed fruit were evaluated. Based on the preliminary results, a mix of cell-free supernatants (CFSs) was applied as a postbiotic solution in minimally processed orange slices packed in a passive atmosphere. Different pathogenic strains were intentionally inoculated to evaluate their antimicrobial effect, and their trend was monitored. Microbiological and physico-chemical analyses were carried out at different times (3, 8, and 10 days) during cold storage. The CFSs obtained from Lactiplantibacillus plantarum and Leuconostoc mesenteroides strains highlighted an antibacterial activity against Escherichia coli and Staphylococcus aureus in both in vitro and in vivo tests, showing a reduction of 1 Log CFU/mL for E. coli and the disappearance of vital S. aureus. In conclusion, the CFSs can be proposed as an eco-friendly biopreservative for orange slices with a clean label, although their stability needs to be evaluated and their limits of application need to be ruled by specific legislation.